“Structures of Feeling”: on tenderness and other sensations in Carlos Gamerro’s fiction - Bollig, B (University of Pennsylvania Press, 2024)
An important aspect of the novels of Carlos Gamerro (Argentina, 1962), largely overlooked by critics, is a subtle and nuanced focus on emotions. This paper begins by outlining the “affective technique” – precise, often metaphorical descriptions, of imprecise, hard to describe feelings – in his early works, acknowledging the many insights of the “affective turn” in Latin American studies. Gamerro’s most recent novels – his Jacobean fiction Cardenio, and La jaula de los onas, based on the history of the Selk'nam, or Ona, people forcibly transported from Tierra del Fuego to be exhibited during the 1889 Paris Exhibition – offer funny and provocative digressions from known historical events but, importantly, rely for their narrative force on a series of moving depictions of human frailty, pleasure, and interdependence. These are linked by a central emotion in Gamerro, namely tenderness. What is more, we find in these novels a “structural tenderness”, and with it a relationship between the vulnerability implicit in this emotion, and a readerly response – an uncertainty or self-doubt – of being pushed into and out of fiction. La jaula de los onas uses this depiction of mutual vulnerability to tell a moving and politically acute story of violence and cultural erasure in the far south.